Nature of Science and Technology-Based Didactical Design on Structure and Physicochemical Property Relationships of Ionic Liquids for Pre-Service Teachers - Devita Marlina Sihite; Ariyatun Ariyatun; Vida Zenitha Sudariasri; Rini Fath Marsya (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
Understanding the Nature of Science and Technology (NOST), as well as strengthening the conceptual mastery of pre-service chemistry teachers by connecting scientific concepts with cutting-edge technological contexts, particularly ionic liquids, remains a challenge in chemistry education. This study aims to design a didactic framework that focuses on the relationship between the structure and physicochemical properties of ionic liquids to develop NOST perspectives and improve conceptual understanding among pre-service chemistry teachers. A descriptive qualitative approach was used with the Didactical Design Research (DDR) model, which includes literature analysis, identification of preconceptions, and mapping of NOST indicators as the foundation for constructing didactic situations. The resulting instructional design is based on seven aspects of NOST to develop relevant didactic situations. Data on NOST perspectives, the seven NOST aspects, and learning barriers were used to design didactic situations, predict responses from pre-service chemistry teachers, and anticipate educators’ actions (ADP). Validation results indicate that this design is feasible to implement, although some improvements are needed regarding language clarity and the appropriateness of learning activities. The implementation of this didactic design has the potential to enhance concept mastery among pre-service chemistry teachers. Pre-test and post-test results show a significant improvement across all sections of the test, with an average increase of 34.3%. These findings demonstrate that a didactic design which considers students’ learning obstacles and the seven aspects of NOST is effective in helping pre-service chemistry teachers actively and systematically build conceptual understanding.